(untitled) (Journal of Nepal Geological Society, 2019)
Armala area of the Kaski District of Nepal is a flat valley of the Kali Khola, which is suffering from sinkhole hazard since 2013. Alarge volume of gravels was transported by the Seti River originated from the Annapurna Range, and the Pokhara Valley and its peripheral regions like the Armala Valley were filled up. The filled-up material in the Armala Valley is calcareous clayey silt with very few gravels. The deposit along the Armala Valley is undergoing subsurface erosion due to flow of subsurface water resulting the formation of subsurface caves and ultimate formation of sinkholes. Present study was concerned about the landform and morphological setting of the area, sediment characteristics and depositional environment of the sinkhole-affected Armala area. Five types of depositional sequences have been identified in the study area; their depositional history and depositional environment also have been interpreted on the basis of the sediment properties as fluvio-lacustrine type. Landform and depositional setting along the study area also seem to influence the sinkhole formation mechanism.